Polyurethane reinforced ballasted track: Review, innovation and challenge. (30th May 2019) - Jing, Guoqing; Qie, Luchao; Markine, Valeri; Jia, Wenli
Highlights: A review of the current research of polyurethane reinforcement in ballasted track. An analysis of the properties of polyurethane and polyurethane-ballast. An investigation of polyurethane reinforcement methods and function. A discussion of challenges and solutions. Abstract: During the development for railway, ballasted track is dominant structure and makes up more than 95% of the whole track modes. However, its shortage is considerable in high speed railway and heavy haul system. Regarding to the ballasted railway track's defects as particle breakage, settlement, and geometry irregularity which lead to enormous maintenance and cost. Polyurethane reinforced ballasted track has shown great application prospect. This reinforcement method can settle several problems, including stiffness adjustment, ballast flight prevention, and stability in specific zones, such as curve, tunnel line. This paper presents a comprehensive review of polyurethane research and application within ballasted track system. Besides, according to different usage, varies of bonding methods are also introduced in this paper. However, some challenges still exist such as maintenance and cost, potential solutions are put forward for further investigated and validated, consequently. Accordingly, an overall prospect of polyurethane reinforcement in railway system is presented.